Tu Youyou winning the Nobel Prize: Ethical research on the value and safety of traditional Chinese medicine - Zheng, Wei-rong (Bioethics, 2020)
In 2015, the Chinese pharmacologist, Tu Youyou, was awarded the Nobel Prize for Physiology or Medicine for the discovery of artemisinin. Traditional Chinese medicine (TCM) was the source of inspiration for Tu's discovery and provides an opportunity for the world to know more about TCM as a source of medical knowledge and practice. In this article, the value of TCM is evaluated from an ethical perspective. The characteristics of ‘jian, bian, yan, lian’ are explored in the way they promote accessibility and economic efficiency for TCM. The article also examines how the increased use and prevalence of TCM reflects the scientific, cultural, and ethical values of TCM and their increasing attraction in meeting major challenges to medicine and health systems currently and in the future. The article discusses safety issues within TCM, which is a controversial area, and also comments on some shortcomings and challenges which pose difficulties for more widespread and greater uptake of TCM-derived clinical or therapeutic interventions. The article concludes that TCM is generally safe if it is used according to TCM theory and where such applications are cognizant of the strengths and weaknesses of TCM. TCM has important bioethical values which may inform potential measures for meeting challenges facing global health care systems and the article argues that it can have an increasing role in improving human health.